FVC, FEV1 and FEV1/FVC% in patients with Major Depressive Disorder - Afreen, Khandaker Nadia; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2016)
Background: Major Depressive Disorder (MDD) is associated with depressed lung function. Objectives: To observe FVC, FEV1 and FEV1/FVC% in Major Depressive Disorder patients. Methods: This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) in 2014on 60 newly diagnosed female MDD patients aged 20 to 50 years. They were enrolled from the Department of Psychiatry of BSMMU. Age, BMI, socioeconomic status and occupation matched 30 apparently healthy females were controls.FVC, FEV1 and FEV1/FVC% were assessed by a portable digital spirometer. For statistical analysis, Independent sample t test was done. Results: FVC, FEV1, FEV1/FVC% were significantly lower (p<0.001) in all MDD patients than those of control. More over, 54(90%) MDD patients had abnormal pulmonary function test. Among them,5(9.25%) had obstructive,32(59.25%) had restrictive and 17(31.48%) had both restrictive and obstructive disorder. Conclusion: From this study it may be concluded that significant depression of lung function may be associated with MDD, characterized by restrictive, obstructive and mixed type disorders. Bangladesh Soc Physiol. 2016, December; 11(2): 59-62